EFFECTIVENESS OF DANCE EXERCISE ON LOW BACK PAIN IN PREGNANT WOMEN: SCOPING REVIEW - Damayanti, Eka; Hidayat, Asri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Lower back pain is a common complaint among pregnant women, which can affect overall quality of life and well-being. Various methods have been proposed to manage this condition, one of which is dance exercise. Aim: This study aims to review the effectiveness of dance exercise in reducing lower back pain in pregnant women. Method : This scoping review follows several steps of the Arksey and O’Malley framework: identification of the research question, identification of relevant studies, study selection, and data collection. Results : Out of 11 studies found, 4 studies met the inclusion criteria. These studies showed that dance exercise can significantly reduce lower back pain and improve mobility and emotional well-being in pregnant women. The most commonly used type of dance was prenatal dance, specifically designed for pregnant women.  Conclusion: Dance exercise is an effective intervention to reduce lower back pain in pregnant women. This exercise not only provides physical benefits but also psychological ones, which are important for holistic well-being during pregnancy. More research is needed to confirm these findings and to develop practical guidelines for its implementation.